Exploring native and non-native English speaker teachers’ perceptions of English teacher qualities and their students’ responses - Deng, Liwei; Zhang, Lawrence Jun; Mohamed, Naashia (Frontiers in Psychology, 2023)
Due to globalization, English has gradually become a lingua franca, leading to a rising demand for proficient English teachers all over the globe. In China, more EFL teachers are being recruited, particularly at the tertiary level, with a greater preference for so-called “native English speaking teachers (NESTs)” over “non-native English-speaking teachers (NNESTs)” due to the impacts of native-speakerism. Research has shown NESTs, NNESTs, and students are often misaligned in terms of beliefs about language learning and teaching which affect teaching effectiveness as well as student achievement. Recognizing this issue, this study investigated NESTs’, NNESTs’, and Chinese English-major students' perceptions of characteristics of effective EFL teachers at four mid-tier universities across China. Findings from semi-structured interviews with 16 students suggest that NNESTs and Chinese English-major students had similar views on language learning and teaching. Both groups valued prerequisite qualities such as having expert knowledge, language skills, teaching skills, and professionalism. NESTs, however, valued qualities such as caring, patience, flexibility, engagement, and awareness of students' learning needs. These differences are likely the result of these two groups of teachers’ linguistic, cultural, and educational background differences. The highly uniform views of the two groups of teachers suggest that they tended to emphasize certain qualities while disregarding others. These findings suggest the need to raise teachers’ and students’ awareness of the benefits of different types of teacher qualities so that curriculum design and lesson planning can be implemented for better instructional alignment to ultimately improve teaching effectiveness.